Pseudomonas aeruginosa isolation from dog grooming products used by private owners or by professional pet grooming salons: prevalence and risk factors. Issue 4 (30th May 2022) - Perry, Elad; Sutton, Gila Abells; Haggag, Lotem; Fleker, Marcelo; Blum, Shlomo Eduardo; Kaufmann, Ronnie
Abstract: Background: Pseudomonas aeruginosa is the most commonly isolated bacterium from skin lesions of dogs with post‐grooming furunculosis (PGF). It is frequently found in human hair and skin care products, and may pose a health risk to consumers . Information regarding the prevalence of P. aeruginosa contamination of dog grooming products is lacking. Objectives: To investigate the prevalence of P. aeruginosa contamination in nonmedicated dog grooming products after either home or professional use in pet grooming salons, and to identify risk factors that may be associated with contamination. Materials and methods: Of 117 bottles of grooming products sampled for bacterial culture, 97 were used by pet grooming salons and 20 were used by private individuals. The following suspected risk factors were recorded: bottle size, relative remaining volume, content dilution, expiration date and ingredient list. Results: Pseudomonas aeruginosa was isolated from 14 of 117 samples [11.97%, 95% confidence interval (CI) 6.97–19.3%]. Diluted products were contaminated significantly more often compared to undiluted products (odds ratio = 15.5, 95%CI 2.05–117.23; P  < 0.01). None of the other variables was significantly associated with P. aeruginosa contamination. Conclusions and clinical relevance: Pseudomonas aeruginosa contamination of dog grooming shampoos and conditioners was significantly associated with product dilution. Contaminated grooming products may predispose dogs to severe bacterial skin infections such as PGF. Abstract : Background – Pseudomonas aeruginosa is the most commonly isolated bacterium from skin lesions of dogs with post‐grooming furunculosis (PGF). It is frequently found in human hair and skin care products, and may pose a health risk to consumers . Information regarding the prevalence of P. aeruginosa contamination of dog grooming products is lacking. Objectives – To investigate the prevalence of P. aeruginosa contamination in nonmedicated dog grooming products after either home or professional use in pet grooming salons, and to identify risk factors that may be associated with contamination. Conclusions and clinical relevance – Pseudomonas aeruginosa contamination of dog grooming shampoos and conditioners was significantly associated with product dilution. Contaminated grooming products may predispose dogs to severe bacterial skin infections such as PGF Résumé: Contexte ‐ Pseudomonas aeruginosa est la bactérie la plus couramment isolée des lésions cutanées des chiens atteints de furonculose post‐toilettage (PGF). On la trouve fréquemment dans les cheveux humains et les produits de soin de la peau et peut présenter un risque pour la santé des consommateurs. Les informations concernant la prévalence de la contamination par P. aeruginosa des produits de toilettage pour chiens font défaut. Objectifs – Étudier la prévalence de la contamination par P. aeruginosa des produits de toilettage pour chiens non médicamenteux après un usage domestique ou professionnel dans les salons de toilettage pour animaux de compagnie, et identifier les facteurs de risque pouvant être associés à la contamination. Matériels et méthodes – Sur 117 flacons de produits de toilettage prélevés pour culture bactérienne, 97 étaient utilisés par des salons de toilettage et 20 par des particuliers. Les facteurs de risque suspectés suivants ont été enregistrés : taille de la bouteille, volume restant relatif, dilution du contenu, date de péremption et liste des ingrédients. Résultats – Pseudomonas aeruginosa a été isolé dans 14 des 117 échantillons [11, 97 %, intervalle de confiance (IC) à 95 % 6, 97–19, 3 %]. Les produits dilués étaient significativement plus souvent contaminés que les produits non dilués (odds ratio = 15, 5, IC à 95 % 2, 05–117, 23 ; P < 0, 01). Aucune des autres variables n'était significativement associée à la contamination par P. aeruginosa . Conclusions et pertinence clinique – La contamination par Pseudomonas aeruginosa des shampoings et après shampoings pour chiens était significativement associée à la dilution du produit. Les produits de toilettage contaminés peuvent prédisposer les chiens à de graves infections cutanées bactériennes telles que la PGF. Resumen: Introducción ‐ Pseudomonas aeruginosa es la bacteria más comúnmente aislada de las lesiones cutáneas de perros con furunculosis posterior al aseado (PGF). Se encuentra con frecuencia en productos para el cuidado de la piel y el cabello humano, y puede representar un riesgo para la salud de los consumidores. Falta información sobre la prevalencia de la contaminación por P. aeruginosa en los productos de aseo para perros. Objetivos ‐ investigar la prevalencia de la contaminación por P. aeruginosa en productos de aseo canino no medicados después del uso doméstico o profesional en salones de aseo de mascotas, e identificar los factores de riesgo que pueden estar asociados con la contaminación. Materiales y métodos ‐ de 117 botellas de productos de aseo muestreados para cultivo bacteriano, 97 fueron utilizados por salones de aseo de mascotas y 20 fueron utilizados por particulares. Se registraron los siguientes factores de riesgo sospechosos: tamaño de la botella, volumen restante relativo, dilución del contenido, fecha de caducidad y lista de ingredientes. Resultados‐ se aisló Pseudomonas aeruginosa en 14 de 117 muestras [11, 97 %, intervalo de confianza (IC) del 95 %: 6, 97–19, 3 %]. Los productos diluidos se contaminaron significativamente más a menudo en comparación con los productos sin diluir (odds ratio = 15, 5, IC del 95 %: 2, 05–117, 23; P < 0, 01). Ninguna de las otras variables se asoció significativamente con la contaminación por P. aeruginosa . Conclusiones y relevancia clínica ‐ la contaminación por Pseudomonas aeruginosa de los champús y acondicionadores de aseo para perros se asoció significativamente con la dilución del producto. Los productos de aseo contaminados pueden predisponer a los perros a infecciones cutáneas bacterianas graves como la PGF. Zusammenfassung: Hintergrund – Pseudomonas aeruginosa ist das am häufigsten isolierte Bakterium aus Hautveränderungen bei Hunden mit einer Furunkulose nach einer Schur (PGF). Es wird häufig in menschlichen Haar‐ und Hautpflegeprodukten gefunden, und könnte ein Gesundheitsrisiko für die KonsumentInnen darstellen. Es gibt keine Information bezüglich der Prävalenz einer P. aeruginosa Kontamination in Pflegeprodukten für Hunde. Ziele – Eine Untersuchung der Prävalenz einer Kontamination durch P. aeruginosa in nicht medizinischen Hunde Pflegeprodukten nach ihrer Verwendung zu Hause oder nach ihrer professionellen Verwendung in Kosmetiksalons für Hunde, sowie eine Identifizierung von Risikofaktoren, die mit einer derartigen Kontaminierung einhergehen könnten. Materialien und Methoden – Von den 117 Flaschen mit Waschprodukten, von denen Proben zur bakteriellen Kultur entnommen wurden, waren 97 in Kosmetiksalons für Tiere im Einsatz und 20 wurden privat benützt. Es wurden die folgenden Risikofaktoren festgehalten: Flaschengröße, relativer Volumensrest, Verdünnung des Inhalts, Ablaufdatum und Zusammensetzung. Ergebnisse ‐ Pseudomonas aeruginosa wurde in 14 von 117 Proben isoliert [11, 97%; 95% Konfidenzintervall (CI) 6, 97‐19, 3%]. Verdünnte Produkte waren signifikant häufiger kontaminiert im Vergleich zu unverdünnten Produkten (Chancenverhältnis = 15, 5; 95% CI 2, 05‐117, 23; P < 0, 01). Keine der anderen Variablen stand mit einer Kontaminierung durch P. aeruginosa signifikant im Zusammenhang. Schlussfolgerungen und klinische Bedeutung – Eine Kontamination von Hundeshampoos und Pflegeprodukten durch Pseudomonas aeruginosa stand in einem signifikanten Zusammenhang mit der Verdünnung der Produkte. Kontaminierte Pflegeprodukte könnten Hunde zu schweren bakteriellen Hautinfektionen wie eine PGF prädisponieren. Abstract : 概要 背景 ‐ 緑膿菌はグルーミング後癤腫症(PGF)の犬の皮膚病変から最もよく分離される細菌である。また、ヒト用のヘアケア製品およびスキンケア製品からも頻繁に検出され、消費者に健康リスクを与える可能性がある。犬用グルーミング製品の緑膿菌汚染の有病率に関する情報は不足している。 目的‐本研究の目的は、家庭用またはペットグルーミングサロンでの業務用使用後の非薬用犬グルーミング製品における緑膿菌汚染の有病率を調査し、汚染と関連しうる危険因子を特定することである。 材料および方法 ‐ 細菌培養のためにサンプリングされたグルーミング製品 117 本のうち、97 本がペットグルーミングサロンで使用されたもの、20 本が個人で使用されたものであった。ボトルサイズ、相対的残量、内容物の希釈度、有効期限、成分表など、リスク要因と思われるものを記録した。 結果 ‐ 117 サンプル中 14 サンプルから緑膿菌が分離された [11.97%, 95% 信頼区間 (CI) 6.97‐19.3%] 。希釈した製品は、希釈していない製品と比べて有意に多く汚染されていた(オッズ比 = 15.5, 95%CI 2.05‐117.23; P < 0.01)。他のどの変数も緑膿菌の汚染と有意な関連はなかった。 結論および臨床的意義 ‐ 犬用グルーミングシャンプーおよびコンディショナーの緑膿菌汚染は、製品の希釈度と有意に関連していた。汚染されたグルーミング製品は、犬を PGF のような重篤な細菌性皮膚感染症にさせる可能性がある。 Abstract : 摘要 背景‐从洗澡后疖病(PGF)患犬的皮肤病变中最常分离出的细菌是铜绿假单胞菌。它常见于人的头发和护肤品中，可能给消费者带来健康风险。缺乏关于犬洗浴产品中铜绿假单胞菌污染流行率的信息。 目的‐研究在家庭中或宠物美容店的专业使用后，非药用犬洗浴产品中铜绿假单胞菌污染的流行率，并确定可能与污染相关的风险因素。 材料和方法‐117瓶洗浴产品用于细菌培养，其中宠物美容店使用的97瓶，私家用的20瓶。记录了以下可疑风险因素:瓶大小、相对剩余体积、内容物稀释度、失效日期和成分列表。 结果‐117份样本中有14份分离出铜绿假单胞菌[11.97%，95%置信区间(CI)6.97‐19.3%]。与未稀释产品相比，稀释产品的污染显著增加(比值比 = 15.5，95%CI 2.05‐117.23；P < 0.01)。其他变量均与铜绿假单胞菌污染无显著相关性。 结论和临床相关性‐犬洗浴香波和护毛素的铜绿假单胞菌污染与产品稀释显著相关。污染的洗浴产品可能使犬易患重度细菌性皮肤感染，如PGF。 Resumo: Contexto ‐ Pseudomonas aeruginosa é a bactéria mais frequentemente isolada de lesões cutâneas de cães com furunculose pós‐banho (FPB). É frequentemente encontrada em cabelos humanos e cosméticos e pode causar malefícios à saúde dos consumidores. Informações sobre a prevalência de contaminação de produtos de banho caninos por P. aeruginosa são escassas. Objetivos – Investigar a prevalência de contaminação de cosméticos de banho não medicamentosos para cães por P. aeruginosa após uso caseiro ou profissional em pet shops, e identificar os fatores de risco que podem estar associados à contaminação. Materiais e métodos – Dos 117 frascos de cosméticos testados por cultura bacteriana, 97 foram utilizados por pet shops e 20 foram de uso doméstico individual. Os seguintes fatores de risco foram registrados: tamanho do frasco, volume remanescente relativo, diluição do conteúdo, data de validade e lista de ingredientes. Resultados ‐ Pseudomonas aeruginosa foi isolada de 14 das 117 amostras [11, 97%, 95% intervalo de confiança (IC) 6, 97–19, 3%]. Produtos diluídos apresentaram contaminação significativamente mais frequentemente, comparado a produtos não diluídos (odds ratio = 15, 5; 95% IC 2, 05–117, 23; P  < 0, 01). Nenhuma das outras variáveis foi significativamente associada à contaminação por P.aeruginosa. Conclusões e relevância clínica – A contaminação de shampoos e condicionadores caninos por Pseudomonas aeruginosa foi significativamente associada à diluição do produto. Cosméticos veterinários contaminados podem predispor cães a infecções cutâneas bacterianas como a FPB.